2017
DOI: 10.1007/s11356-017-0179-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of antifungal peptides from Bacillus amyloliquefaciens W10

Abstract: Antifungal metabolites produced by Bacillus sp. W10, which was previously isolated from the tomato rhizosphere, were investigated. Strain W10 was identified as Bacillus amyloliquefaciens by analysis of its 16S rDNA and gyrB gene partial sequences. PCR analysis showed the presence of fenB, sfp, and ituD genes, coding for fengycin, surfactin, and iturin, respectively. A novel small antifungal peptide, designated 5240, produced by this strain was isolated by ammonium sulfate precipitation and Superdex 200 gel fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…All the studies reported the antibiosis of B. cinerea by the NRPs metabolites produced by B. subtilis but do not demonstrate directly the implications of these molecules in the antibiosis ( Tareq et al, 2014 ; Farace et al, 2015 ; Wang et al, 2015 ; Arroyave-Toro et al, 2017 ). The same occurs with B. amyloliquefaciens ( Ji et al, 2013 ; Pretorius et al, 2015 ; Tanaka et al, 2015 ; Zhang et al, 2017 ), B. marinus ( Gu et al, 2017 ), B. atrophaeus ( Zhang et al, 2013 ), and B. velezensis ( Ge et al, 2016 ; Romero et al, 2016 ; Gao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…All the studies reported the antibiosis of B. cinerea by the NRPs metabolites produced by B. subtilis but do not demonstrate directly the implications of these molecules in the antibiosis ( Tareq et al, 2014 ; Farace et al, 2015 ; Wang et al, 2015 ; Arroyave-Toro et al, 2017 ). The same occurs with B. amyloliquefaciens ( Ji et al, 2013 ; Pretorius et al, 2015 ; Tanaka et al, 2015 ; Zhang et al, 2017 ), B. marinus ( Gu et al, 2017 ), B. atrophaeus ( Zhang et al, 2013 ), and B. velezensis ( Ge et al, 2016 ; Romero et al, 2016 ; Gao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 63%
“…With respect to the activity of lipopeptides, Romano et al (2013) reported the non-effect of B. amyloliquefaciens lipopeptides against B. cinerea at concentrations of 0.1 mg mL -1 . Tareq et al (2014) established a range of lipopeptide activity in B. subtilis between 0.5 to 300 μg mL -1 and Zhang et al (2017) determined the maximum activity of lipopeptides of B. amyloliquefaciens at 30 mg mL -1 . Our study tested a range of concentrations from 0.5 to 20 mg mL -1 and confirmed the antifungal activity of XT1 lipopeptides with inhibitory and fungicidal effects of these compounds at concentrations as low as 8 mg mL -1 (MIC and MFC).…”
Section: Discussionmentioning
confidence: 99%
“…These molecules insert themselves into the microbial cell membranes, or chelating cations. This effect alters the membrane permeability, eventually disrupting it and causing cell swelling and death ( Zhang et al, 2017 ; Zhao et al, 2017 ).…”
Section: Methods For Controlling Biofilm Formation In the Food Industmentioning
confidence: 99%
“…The structure of the peptide cycle combines with a long fatty acid chain to produce an amphiphilic trait, which determines the most suitable target sites on the cellular membranes(10). In addition, due to its variety and the number of amino acids as well as the diversity of fatty acid chain length, CLPs have multiple homologs(11). Moreover, CLPs derived from Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CLPs derived from Bacillus spp. can be classified into three main subfamilies: iturin, surfactin, and fengycin(1113). Interestingly, surfactin has powerful antiviral activities but low activities against bacteria and fungi(14), while iturin and fengycin exhibit an obvious antifungal activity against a range of filamentous fungi(9, 15).…”
Section: Introductionmentioning
confidence: 99%